Daya Terima Masyarakat Terhadap Keberadaan Perusahaan Dengan Pendekatan (Social License To Operate) Di Desa Tani Baru Kecamatan Anggana - Suprapto, Heru; Akbar, Ali; Sundoyo, Sundoyo; Martain, Martain; Raharjo, Sugeng; Efendi, Aswan (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2023)
Abstract Research on Community Acceptance of the Company's Existence weaving the SLO instrument developed by Thomson and Boutilier (2011), the research uses a two-stage qualitative approach, the first uses a benchmark of SLO perception value then the findings are confirmed to key stakeholders. The results showed that SLO is at Acceptance/high tolerance, i.e. that the company has crossed the threshold of legitimacy to operate. High acceptance/tolerance is a temporary willingness to tolerate the company's operations, thus the company's operating environment is not stable with the potential for turmoil that can be disruptive.